Improving dribbling performance through ladder drill training in youth football players - Gatot Margisal Utomo; Eka Kurnia Darisman (Mamaos: Journal Physical Education, Sport and Art, 2026)
This study aimed to examine the effect of ladder drill training on dribbling performance in youth football players. A pre-experimental one-group pretest–posttest design was employed involving 20 players from SSB Untag Rosita Surabaya. Dribbling performance was assessed using a cone-based dribbling test in which players completed a timed course. The intervention consisted of structured ladder drill training integrated into regular training sessions over a three-month period. Data were analyzed using descriptive statistics and a paired sample t-test at a significance level of p < 0.05.The results showed a significant improvement in dribbling performance following the intervention. The mean dribbling time decreased from 18.54 seconds in the pretest to 15.61 seconds in the posttest, with an average improvement of 2.93 seconds. Statistical analysis confirmed a significant difference between pretest and posttest scores (p < 0.05). The findings indicate that ladder drill training effectively enhances agility, coordination, and movement control, which contribute to improved dribbling performance. In conclusion, ladder drill training represents a practical and effective method for improving dribbling performance in youth football players and can be integrated into regular training programs to support technical development.